Human induced pluripotent stem cell derived neurons as a model for Williams-Beuren syndrome. Issue 1 (December 2015) - Khattak, Shahryar; Brimble, Elise; Zhang, Wenbo; Zaslavsky, Kirill; Strong, Emma; Ross, P.; Hendry, Jason; Mital, Seema; Salter, Michael; Osborne, Lucy; Ellis, James
Abstract Background Williams-Beuren Syndrome (WBS) is caused by the microdeletion of approximately 25 genes on chromosome 7q11.23, and is characterized by a spectrum of cognitive and behavioural features. Results We generated cortical neurons from a WBS individual and unaffected (WT) control by directed differentiation of induced pluripotent stem cells (iPSCs). Single cell mRNA analyses and immunostaining demonstrated very efficient production of differentiated cells expressing markers of mature neurons of mixed subtypes and from multiple cortical layers. We found that there was a profound alteration in action potentials, with significantly prolonged WBS repolarization times and a WBS deficit in voltage-activated K+ currents. Miniature excitatory synaptic currents were normal, indicating that unitary excitatory synaptic transmission was not altered. Gene expression profiling identified 136 negatively enriched gene sets in WBS compared to WT neurons including gene sets involved in neurotransmitter receptor activity, synaptic assembly, and potassium channel complexes. Conclusions Our findings provide insight into gene dysregulation and electrophysiological defects in WBS patient neurons.